2015
DOI: 10.1155/2015/397069
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate Adsorption on Clay Kaolin: Batch Tests

Abstract: Soils possessing kaolin, gibbsite, goethite, and hematite particles have been found to have a natural capacity to attenuate pollution in aqueous phase. On the other hand, the hydroxyl group in soil increases anion exchange capacity under a low pH condition. The main objective of this paper was to evaluate effects of kaolin on nitrate reduction under acidic condition. In order to analyze the kaolin adsorption behaviour under various conditions, four different concentrations of nitrate, 45, 112.5, 225, and 450 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 29 publications
2
18
0
Order By: Relevance
“…Uzoho et al [45] reported different correlations between nitrates and clay content in soil. Correlation results suggest that some nitrate concentration is bound to clay particles of studied soil, which is consistent with research of Mohsenipour et al [46]. In this case, it is possible that some part of nitrate can be adsorbed to clay particles, which results in lower nitrate concentrations in the deeper part of the soil profile, but also in the Zagreb aquifer [38,39].…”
Section: Ph (Kcl)supporting
confidence: 91%
“…Uzoho et al [45] reported different correlations between nitrates and clay content in soil. Correlation results suggest that some nitrate concentration is bound to clay particles of studied soil, which is consistent with research of Mohsenipour et al [46]. In this case, it is possible that some part of nitrate can be adsorbed to clay particles, which results in lower nitrate concentrations in the deeper part of the soil profile, but also in the Zagreb aquifer [38,39].…”
Section: Ph (Kcl)supporting
confidence: 91%
“…By ignoring the extremely low and large value of concentrations, the model assumes that heat of adsorption (function of temperature) of all molecules in the layer would decrease linearly rather than logarithmic with coverage [28]. As implied in (15), its derivation is characterized by a uniform distribution of binding energies (up to some maximum binding energy)…”
Section: Temkin Isothermmentioning
confidence: 99%
“…Kaolin can be found abundantly in Nigeria where it is mainly used for porcelain production and has been investigated and found to be effective in the removal of toxic metals from waste water [14]. It was found to be effective in the adsorption of methylene blue [13], nitrate [15], hexavalent chromium [16], Congo Red [17] from aqueous solution. This report investigated and compared the zinc adsorptive strength of cassava peels activated carbon and raw kaolin clay.…”
mentioning
confidence: 99%
“…Nitrate in contaminated water can be removed from aqueous phase generally by biological reduction to convert N 2 6) and adsorption to solid surfaces 7) including ion exchange. 8) Adsorptive removal was conducted by chitosan, 9) sepiolite, 10) kaolin, 11) functionalized silica, 12) activated carbon, 13) carbon nanotube (CNT) 14) and many other natural and synthesized materials. 7) In this study commercially available activated carbon (AC) was firstly oxidized so as to maximize oxygen content and then pure NH 3 gas treatment was conducted to increase positively charged quaternary nitrogen (N-Q, N + ) on the carbon surface 15) to improve adsorption affinity and capacity of nitrate anion.…”
mentioning
confidence: 99%